Managing the China, India and Pakistan Nuclear Trilemma: Ensuring Nuclear Stability in the New Nuclear Age - Rakesh Sood (Journal for Peace and Nuclear Disarmament, 2022)
The beginning of the nuclear age coincided with the beginning of the Cold War. The politics of the bipolar world, with two nuclear hegemons enjoying nuclear superpower status, shaped the nuclear order. At one level, it would appear to be a success because it helped create and sustain a nuclear taboo that has lasted for 75 years. However, the world has changed. The notions of “nuclear parity” and “mutual vulnerability” that made it possible to reduce strategic stability to nuclear stability and created the enabling conditions for bilateral nuclear arms control have given way to asymmetry with nuclear multipolarity. This has led to the unravelling of the old arms control mechanisms and a concern that the nuclear taboo may be eroding. The United States and the USSR had no territorial disputes; instead, their rivalry played out in the form of proxy wars. Today, nuclear rivals are often neighbours. Their disputes relate to issues of national sovereignty. Further, nuclear dyads have given way to trilemmas and nuclear chains. Technological developments generate further challenges for arms control. More usable nuclear weapons, dual use systems, a renewed offence-defence spiral with missile defences and hypersonics, and growing offensive cyber and space capabilities that make for nuclear entanglement demand a fresh look at arms control and nuclear stability. In the China-India-Pakistan trilemma, proposals have to take cognisance of the new political realities to break out of the cycle of mistrust and reduce risks of both misperceptions and miscalculation that could lead to inadvertent escalation.